The influence of vertical muscles surgery on refraction and visual acuity - Risović Dušica J. (Vojnosanitetski Pregled)
Background. The aim of this paper was to determine whether the surgery on vertical muscles of the eye influenced the change in refraction and visual acuity. Methods. This prospective study included testing of 79 children with infantile esotropia who suffered from the vertical strabismus after the surgery on horizontal muscles. Patients were divided into two groups: the first group of 52 children (the test group) had only vertical component (overaction of m. obliqui inferior) and the second group (the control group) had two vertical components (dissociated vertical deviation - DVD and overaction of m. obliqui inferior). Refraction and visual acuity were tested before the surgery on the vertical muscles and one month and six months after the surgery. There was no significant difference between the results of the objective refraction in those three different periods of time. Results. In both groups mild hypermetria (according to Costenbander) occurred in 40-48% of the examinees of both groups, while moderately-expressed hypermetropia occurred in 40-50% of the examinees. There was neither statistically significant difference between the results of the three observed measurings among every group, nor between the observed groups of patients (p>0,05). By the analysis of the results of visual acuity it could be concluded that it was significantly improved 6 months after the surgery on cyclovertical muscles. This change was more significant in the sample group of patients (p<0,01) than in the children from the control group (p<0,05), who were much older. Conclusion. Objective refraction in patients was in the range of low values of hypermetropia (+2.00 Dsph - t 3.00 Dsph). Significant improvement of visual acuity occurred 6 months after the surgery performed on vertical muscles of the eye. These results were achieved by the repeated measuring of objective refraction and the precise correction of every new accommodative element.